Analgesic Efficacy of Ibuprofen in Dysmenorrhea - Safa DÖNMEZ; Alp ŞENER; Ahmet Burak ERDEM; Çağlar ÇETİN; Gülhan KURTOĞLU ÇELİK (Bezmiâlem Science, 2023)

(untitled)
Objective:Non-steroidal anti-inflammatory drugs (NSAIDs) are used routinely and as first choice in the analgesic treatment of abdominal pain caused by primary dysmenorrhea (PD). In our study, we aimed to compare the analgesic efficacy of 400 mg and 800 mg ibuprofen doses administered intravenously (iv) in the treatment of patients presenting with abdominal pain due to PD.Methods:The study was conducted in emergency department over a period of 4 months in a prospective, randomized, controlled and single-blind design. Females aged between 18-50 years were included in the study. The patients were randomly divided into two groups as those who received ibuprofen 400 mg and those who received 800 mg. In these two groups, the pain scores of the patients at 0, 30 and 60 min were determined and analyzed using the 10-unit Numeric Rating Scale (NRS).Results:A total of 54 patients, 27 in each group were included in the study. Age, weight and body mass index parameters of the groups were statistically similar. There was no statistically significant difference between the two groups in terms of the degree of pain at admission and at the 30th-60th min of follow-up. In the 400 mg and 800 mg treatment groups, the NRS score differences between 0 and30 min periods [median [interquartile range (IQR): 4 (3-5) and 4 (3-4); p=0.224] and between 0 and 60 min periods [median (IQR): 4 (3-5) and 4 (3-4); p=0.224] were statistically similar. There was no difference between the two groups in terms of need for rescue medication and side effects.Conclusion:Similar efficacy is observed in reducing pain intensity between 400 mg and 800 mg doses of iv ibuprofen. According to these findings, it can be concluded that 400 mg of ibuprofen IV preparation can be preferred over 800 mg in the treatment of abdominal pain in patients with PD.